Factors of affecting business opportunities in developing ecotourism - Simarmata, Marulam MT.; Astuti, Tri (International research journal of management, IT and social sciences, 2020)
This tourism science study aims to identify what factors affect business opportunities to develop the creative economy of the tourism sector in the Lumbang Julu Regency. With this identification, the tourism development sector will be able to play its role, improving the economy of the local community. For this reason, it is necessary to have an effort such as a study to identify what factors need to be prioritized in developing tourism in a tourist destination. To realize the development of tourism, especially the potential and factors that affect business. A series of searches and data collection through field observations, a survey of 175 visitors, and a study of related literature were carried out. The way to collect data is to ask what the tourists’ goals are, what situation they like, and previous tourist experiences in other places. After the data has been collected, it is then continued with analysis using a descriptive qualitative and quantitative combined method approach with an emphasis on 5 indicators that will influence entrepreneurial success in Lumbang District.